Serum fatty acid reference ranges: percentiles from a New Zealand national nutrition survey. - Bradbury, K; Skeaff, C; Crowe, F; Green, T; Hodson, L (2011)
Serum fatty acids are increasingly used in cross-sectional surveys and cohort studies as biomarkers of dietary fat intake; however, it is currently difficult to judge whether an individual has low or high fatty acid status, or whether the distribution of fatty acids of a group of people is low or high due to a lack of appropriate reference values. In the absence of interpretive criteria, the distribution of serum fatty acids from a suitable reference population can be used as an alternative. We describe the distribution of the fatty acid composition of the three most commonly reported lipid classes in serum; cholesterol ester, phospholipid and triacylgycerol. Results for each serum lipid class are presented as means (SD) and percentiles (5, 10, 25, 50, 75, 90, and 95) of serum fatty acids in non-fasting blood samples collected from a population based cross-sectional survey of New Zealand adults (n = 2793). These serum fatty acid reference ranges are applicable and relevant to Australia, United Kingdom, and United States as well as other countries where fat intakes are similar to New Zealand.